Sine cosine optimization based multilevel segmentation of digital images - Rakoth Kandan, S; Srinivas Rao, P; Durgalakshmi, B (International Journal of Engineering and Technology, 2018)
This main objective of this paper is to present a sine-cosine optimization algorithm for multilevel segmentation of real-time and medical images. It chooses the threshold values for all R, G, B channels of real life and medical images through effectively exploring the solution space in obtaining the global best solution. The results are compared with existing methods and finally, the proposed method is able to offer better segmentation results than that of an existing method.
Keywords: Image Processing; Multilevel Segmentation; Optimization.